(untitled) (Journal of Pharmaceutical Negative Results, 2023)
This article discusses in detail the rapid development of the 3D modeling process, 3D modeling software, and the role of 3D printing technologies and materials in our lives. The wide range of uses of 3D printing, scope of possibilities, benefits and possible dangers are explained. The "plastic-sand" material obtained from the new, environmentally friendly plastics of the modern era, its components, production technology were explained and the possibility of its use as a 3D printing material was suggested. Advantages and disadvantages of the material, areas of exploitation were investigated, suggestions were made about the already used and to be designed "plastic-sand" products. The main goal of the article is to protect our countries from "plastic pollution" and to use plastic waste in recycling. One of the steps taken in this direction is the preparation of "plastic-sand" materials obtained from the recycling of plastic waste (containers, packages, boxes, etc.) and their use in 3D printers. In this regard, since the protection of ecological safety of the environment is a very important issue, the article considers the design of new technologies for collecting and recycling plastics that harm human health and cause pollution of nature. Thus, a new proposal was proposed to produce "plastic-sand" material, to produce eco-friendly and low-cost products, important in our daily life, with an aesthetic appearance, complex shape and construction. The most important thing is to attract investors to open workshops and production facilities for the purpose of developing new technology in this field. At the same time, the proposed project will protect the ecological safety of nature, and will allow to buy cheaper products.